Heliothrips haemorrhoidalis and its relatives, with one new species and one new genus (Thysanoptera: Thripidae) - Nakahara, Steve; O’donnell, Cheryle A.; Mound, Laurence A. (Zootaxa, 2015)
Heliothrips similis sp.n. is described as a close relative of the greenhouse thrips, Heliothrips haemorrhoidalis. This is the third species recognized here in the Neotropical genus Heliothrips. A pest species described from South Africa as Heliothrips sylvanus is transferred to a new genus, Neoheliothrips gen.n., as Neoheliothrips sylvanus (Faure) comb.n.